The Level of Environmental Awareness among Students of the Faculty of Educational Sciences at Al-Quds Open University and their Attitudes Towards it (Palestine Technical College Journal for Research and Studies, 2020)
The present study aimed at measuring the level of environmental awareness among the students of the Faculty of Educational Sciences at Al-Quds Open University and their attitudes towards it. The descriptive analytical approach was followed on a sample of (172) male and female students from the Faculty of Educational Sciences in the academic year 2017/2018. To collect the data of the study, a (45) item questionnaire was used to measure the environmental awareness besides a (34) scale to measure the students’ attitudes towards it. T study concluded the low level of environmental awareness among the study sample, as only (9.3%) among the students who reached (60% and above) on the environmental awareness scale. It is worth mentioning that the percentage of environmental awareness was compared to the hypothetical percentage (60%). The results also showed that those who have no environmental awareness (cut off less than 60%) reached (90.7%), while the rest had environmental awareness (9.3%). Additionally, there are statistically significant differences of the total sample in favor of males in the level of environmental awareness, where the mean of the male was (52.5). Moreover, the results revealed that those who have positive attitudes towards environmental awareness reached (14.5%), while those who did not have positive attitudes towards environmental awareness reached (85.5%). Finally, there are no statistically significant differences between the attitudes of the students neither due to their gender nor due to the level of the trend towards environmental awareness.
Keywords: Environment; Awareness; Attitudes; Al-Quds Open University